Trascendenza umana e libertà dell’Essere: prospettive dell’interpretazione heideggeriana di Kant a partire da Vom Wesen der menschlichen Freiheit: Einleitung in die Philosophie (SS 1930) - La Bella, Laura (Scenari, 2021)
The aim of this article is to take into examination Heidegger’s treatment of the question concerning human freedom, as it results from his 1930 lecture course Vom Wesen der menschlichen Freiheit. Einleitung in die Philosophie, in which Heidegger’s reading of Kant’s Critiques leads him to emphasize the ontological limits of Kant’s conception of transcendental and practical freedom. The essential connection that he recognizes between the concepts of Kausalität and Bewegung allows Heidegger to argue that Kant’s notion of human freedom, as rooted in the cause/effect relation that is constitutive of all natural phenomena, ultimately falls back into a metaphysical perspective of Aristotelian origins, marked by the category of Vorhandenheit, and implies an inauthentic understanding of the essence of the human being. Moving from this critical interpretation of Kant’s practical philosophy, I will emphasize how the “philosophic torsion” invoked by Heidegger in the last pages of his abovementioned work thus expresses an urge to stop interpreting freedom from a merely anthropological perspective and, vice-versa, to start identifying the essence of the Dasein with the place in which the freedom of Being manifests itself.